Media Pembelajaran Interaktif Berbantu Software Lectora inspire - Nursidik, Hamidah; Suri, Indah Resti Ayuni (Universitas Islam Negeri Raden Intan Lampung, 2018)
This research and development aims to know the prevalence of interactive learning media products assisted software lectora inspire and to know the response of learners to interactive learning media assisted software lectora inspire on material relations and functions that have been developed. The method used in this research is 7 stages from 10 stages of research and development method from Brog and Gall which have been modified by sugiyono. The stages are potential and problems, data collection, product design, validation, design improvement, product testing, and product revision. Instrument data collection used is validation sheet and questionnaire response of learners. Based on the results of the study showed: Interactive learning media assisted software lectora inspire on material relations and class X functions developed with Brog and Gall modified by sugiyono declared feasible to be used by experts materials and media experts with good criteria with assessment of average material experts 4,2 and the media expert 3,5. Student response to interactive learning media assisted software lectora inspire on material relation and function get good criterion with average value 4,0167.